Antiviral bioactivity of resveratrol against Zika virus infection in human retinal pigment epithelial cells - Russo, Constanza A. (2021)
Resveratrol (RES) is a polyphenol with increasing interest for its inhibitory effects on a wide variety of viruses. Zika virus (ZIKV) is an arbovirus which causes a broad spectrum of ophthalmological manifestations in humans. Currently there is no certified therapy or vaccine to treat it, thus it has become a major global health threat. Retinal pigment epithelium (RPE) is highly permissive and susceptible to ZIKV. This work explored the protective effects of RES on ZIKV-infected human RPE cells. RES treatment resulted in a significant reduction of infectious viral particles in infected male ARPE-19 and female hTERT-RPE1 cells. This protection was positively influenced by the action of RES on mitochondrial dynamics. Also, docking studies predicted that RES has a high affinity for two enzymes of the rate-limiting steps of pyrimidine and purine biosynthesis and viral polymerase. This evidence suggests that RES might be a potential antiviral agent to treat ZIKV-induced ocular abnormalities.